(untitled) (Journal of the College of Basic Education, 2024)
This study is an endeavour to investigate the efficacy of Cognitive Grammar in the Kurdish context compared to the traditional approaches to teaching selected grammar topics, namely English tense and aspect, passivization and modal auxiliary verbs at tertiary level. Cognitive Grammar is one of the major approaches within the framework of Cognitive Linguistics to the structures and meanings of grammar and has two crucial guiding principles: the symbolic commitment and usage-based commitment. The study is a Quasi-experimental and has used a pre-test and post-test as its main tool for collecting its data. Its participants were comprised of (54) junior EFL university students divided into two equal intact groups (A and B) with (27) students in each. Group (A) was randomly assigned as the Control group and (B) as the Experimental group of the study. Both the Experimental and Control groups were exposed to a full semester of teaching treatments based on Cognitive Grammar instruction and traditional instruction respectively to teaching the aforementioned grammatical phenomena. The Independent Samples t-test was used to analyze the data through the Statistical Package for the Social Sciences SPSS. It was found that there was a statistically significant difference between the post-test mean scores of the two groups as the Experimental group (M = 33.18) had outperformed the Control group (M = 24.96). It was also found that the Cognitive Grammar-grounded instruction was more effective and significantly enhanced the achievements of the participants in tense and aspect and the modal verbs. The study has ended with a conclusion and some recommendations for further study.